Increased Transforming Growth Factor‐β Levels Associated With Cardiac Adverse Events in Hypertrophic Cardiomyopathy - Ayça, Burak (Clin Cardiol, 2015)
BACKGROUND: Hypertrophic cardiomyopathy (HCM) is a common genetic heart disease characterized by ventricular hypertrophy, myocardial fibrosis, and impaired ventricular relaxation. The exact mechanisms by which fibrosis is caused remain unknown. HYPOTHESIS: Circulating TGF‐β is related to poor prognosis in HCM. METHODS: We compared TGF‐β levels of 49 HCM patients with those of 40 non‐HCM patients. We followed the patients with HCM for 18 months and divided them into 2 groups: low TGF‐β (≤4877 pg/mL) and high TGF‐β (>4877 pg/mL). We compared the 2 groups in terms of brain natriuretic peptide (BNP), echocardiographic parameters, and clinical outcomes including myocardial infarction, arrhythmias, implantable cardioverter‐defibrillator implantation, hospitalization, New York Heart Association (NYHA) class, acute heart failure, and mortality. RESULTS: The HCM patients had higher TGF‐β levels than those in the control group (P = 0.005). In the follow‐up, those in the high TGF‐β group had higher BNP levels, larger left‐atrial size, thicker interventricular septum, NYHA class, more hospitalizations, and a greater number of clinical adverse events (P < 0.001, P = 0.01, P < 0.001, P = 0.002, P < 0.001 and P = 0.003, respectively). TGF‐β level of >4877 pg/mL can predict adverse events with a specificity of 75% and a sensitivity of 72% (P = 0.014). In multivariate regression analysis, TGF‐β, BNP, and interventricular septum thickness were significantly associated with adverse events (P = 0.028, P = 0.030, and P = 0.034, respectively). CONCLUSIONS: The TGF‐β level is higher in HCM patients and associated with a poor prognosis in HCM.